STRATEGI PERTAHANAN LAUT INDONESIA MELALUI MODERNISASI ALUTSISTA TNI AL - Siregar, Hendra; Achnaf, M. (Journal of Industrial Engineering & Management Research, 2022)
This research method uses a literature study with a descriptive qualitative approach. Data collection techniques using literature study. The data analysis technique of this research is interactive model of analysis which consists of three components of analysis, namely Milles and Huberman, namely reduction, presentation and conclusion. The results of the study stated that the modernization of the defense equipment system as an effort to carry out Indonesia’s maritime defense strategy is an urgent matter considering the threat posed by the enemy is very dangerous. They are also modernizing their defense equipment. Foreign countries that can threaten the territory of Indonesia show the progress of their defense equipment. In addition, crimes in Indonesia’s marine areas such as illegal fishing, piracy, terrorism, people smuggling also improve the quality of ships and their equipment so that they are not detected by patrols. Thus, Indonesia’s maritime defense strategy cannot be separated from efforts to modernize the Indonesian Navy’s defense equipment. The government through the Ministry of Defense must design the modernization of the defense equipment system by taking at least three strategies or policies, namely the budget strategy, investment strategy, and procurement strategy.